Cost-related underuse of medications in older adults: ELSI-Brazil - Loyola Filho, Antônio Ignácio de; Firmo, Josélia Oliveira Araújo; Mambrini, Juliana Vaz de Melo; Peixoto, Sérgio Viana; Souza Junior, Paulo Roberto Borges de; Andrade, Fabíola Bof de; Lima-Costa, Maria Fernanda; Acúrcio, Francisco de Assis (Revista de Saúde Pública, 2019)
OBJECTIVE: To assess the prevalence and factors associated with cost-related underuse of medications in a nationally representative sample of Brazilians aged 50 years and over. METHODS: Among the 9,412 participants of the Brazilian Longitudinal Study of Aging (ELSIBrazil), 6,014 reported using at least one medication on regular basis and were included in the analysis. Underuse of medications was by stopping taking or reducing the number of tablets or the dose of any prescribed medication for financial reasons. The theoretical framework used for the selection of the exploratory variables included predisposing factors, enabling factors, and factors of need. Associations were tested by Poisson regression. RESULTS: The prevalence of underuse of medications was 10.6%. After adjustments for relevant covariables, positive and statistically significant associations (p < 0.05) with the outcome were found for females [prevalence ratio (PR) = 1.39], sufficiency of the family income for expenses (PR = 1.74 for sometimes and PR 2.42 for never), frequency with which the physician explains about the disease and treatment (PR = 1.31 for rarely or never), number of medications used (PR = 1.39 for 2–4 and 1.53 for 5 or more), fair (PR = 2.02) and poor or very poor self-rated health (PR = 2.92), and a previous medical diagnosis of depression (PR = 1.69). Negative associations were observed for the age groups of 60–79 years (PR = 0.75) and 80 years and over (PR = 0.43), socioeconomic status of the household (PR = 0.70, 0.79, and 0.60 for the second, third, and fourth quartile, respectively), and private health plan coverage (PR = 0.79). There were no associations between hypertension and self-reported diabetes and underuse of medications. CONCLUSIONS: Cost-related underuse of medications is multidimensional and complex, and it covers socio-demographic characteristics, health conditions, and the use of health services. The explanation about the disease and its treatment to the patient and the expansion of the universal access to pharmaceutical care can minimize the risks of underuse.